Chronic Diffuse Alopecia In Female - Roy Aloke K; Ghosh Sadhan K; Mitra Pradip K; Bhattacharya Gora C; Chakraborty Indranil (Wolters Kluwer Medknow Publications, 1997)
Fifty female patients, in the age range 3.5 to 45 yrs, suffering from chronic diffuse alopecia were studied for the probable causes. In 26% of cases, iron deficiency anaemia was found to be the major aetiological factor and 20% cases showed hupothyroidism. The cause could not be traced in 40% of cases. In majority of cases, multiple factors might be implicated.